A mass spectrometric examination of some carbohydrates - Peltier, John M. (My University, 1992)
Many carbohydrates have useful biological properties, which has generated interest in the structural elucidation of this class of compounds. One technique that has been applied successfully to the structural elucidation of carbohydrates and carbohydrate derivatives is mass spectrometry (MS). In this research a number of peracetylated and pertrideuteroacetylated mono- and disaccharides were examined by ammonia desorption chemical ionization (NH₃-DCI) in order to gain insight into the fragmentation processes and to assess the structural information available in the NH₃-DCI mass spectra. As a result of these studies a new method has been developed to determine the position of linkage in peracetylated disaccharides comprised of hexopyranose (glucose or mannose) units by use of mass-analyzed ion kinetic energy (MIKE) scans. The second part of this thesis deals with the structural elucidation of the core portion (core) of the lipopolysaccharides (LPS) derived from two mutants (AK1012 and AK1401) of the bacterium Pseudomonas aeruginosa, a ubiquitous opportunistic pathogen, which is resistant to antibiotic therapy. Since LPS are the principal antigenic determinants of this bacterium a knowledge of the structure of the LPS is important in the development of synthetic vaccines. In this work mass spectrometry, in conjunction with a number of chemical and chromatographic techniques, was applied to the structural elucidation of the AK1012 core and AK1401 core. The combination of methods applied to this problem resulted in the elucidation of many of the structural features of these carbohydrates; however, some aspects of the structure remain unknown.
Keywords: Chemistry; Chemistry